(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Introduction :The diagnosis of sudden death due to acute Myocardial Infarction (MI) is difficult not only for forensic expert but for pathologist as on gross examination one may not find infarct area. So most of the time cause of death cannot be given in these cases. Aim: This study has been undertaken to determine the usefulness, efficiency and reliability of new technique (TTC) to determine changes of ischemia during the autopsy along with routine histological examination by H&E stain. Material and Methods: Present prospective study was carried out on 60cases of sudden cardiac death cases. The heart was examined & the slices of muscular wall were incubated inTri phenyl Tetrazolium Chloride stainingfor 20-30min for any change of ischemia. Unstained slice were read as positive and bright pink stained as negative, Appropriate sections were taken for histopathological confirmation. Results: Out of 60 cases , 15 (25%) cases show positive TTC staining and in all positive cases there was histopathological change as acute myocardial infarction in 13 cases and healed myocardial infarction in 2 cases .In coronary arteries, Grade VI atherosclerosis was most commonly seen on histopathological examination, Common age group affected was 46 – 55 years (Mean 50.5 years) followed by 36 - 45 years. Male outnumbered the females. Conclusion: TTC staining technique is more sensitive & efficient method for detection of early ischemic changes in cases of sudden death.